A Descriptive Study On Students' Ability In Writing Recount Text At The Eight Grade Of SMP N 2 Colomadu In 2013/2014 Academic Year - Utami, Henny Sulistyani; , Drs. Djoko Srijono, M. Hum; , Dr. Dwi Haryanti, M.Hum (2014)
The aim of this research is analyzing the students' ability in writing recount text of the eight grade of SMP N 2 Colomadu in 2013/2014 academic year and to find the problems faced by the students in writing recount text. This research is a descriptive study. The methods of collecting data are writing test and document. Data of the research are the student works in writing recount text. Data sources of the research are informant and writing test. The techniques of analyzing data are (1) collecting the data from the student works in writing recount text, (2) analyzing the data based on the criteria of writing recount text, (3) discussing the result of research based on the data from the previous step, and (4) drawing conclusion and giving suggestion. Based on the analyzed data, it can be concluded that the students' ability in writing recount text at the eight grade of SMP N 2 Colomadu is categorized in three categories. There are 14 students who belong to the good category (41,18%), 19 students who belong to the fair category (55,88%), and 1 student who belongs to the poor category (2,94%). The problems faced by the students are grammar and mechanism, where grammar is the main problem with the highest mistakes made by the students.